Analysis of modernization and improvement factors of tourism industry in Qibla, Lahich, Khinaliq cities of Ghobakhachmaz province of Azerbaijan for mapping tourism attraction program based on structural equation model - tavakoli, Arman mahdavi; Aliyeva, Rahiba (The journal of contemporary issues in business and government, 2021)
The historical heritage of any country is a tangible asset that, in addition to preserving the identity and culture of that region, causes the development of the tourism industry and the nature of the economic cycle. The tourism industry with potential impact on the economy of any country is one of the categories of interest. In this article, the main purpose of using strategies to recreate historical contexts as a valuable asset for renovation and improvement so that the tourism industry develops in these areas. Meanwhile, the historical cities of Qibla, Lahij and Khinaliq in Qubakhachmaz province of the Republic of Azerbaijan, with their historical and valuable texture and the presence of attractive tourist potentials, need to be restored, protected and maintained in order to develop the tourism industry; In this research, according to the purpose of these three areas will be examined. The research method in this article is descriptive- analytical. Also, the factors were weighted using level one and two factor analysis methods. Findings show that, experts consider government participation in the development of recreational space as the first priority, development of local economy, social interaction and maintenance and restoration of places as the second priority, attention to the introduction of culture and values, third priority and attention to advertising And they prioritized its nature in introducing places as the fourth priority.